Identifikasi dan Analisis Ketahanan terhadap Penyakit Embun Tepung pada Melon (Cucumis melo L.) Kultivar Meloni - Muhammad Alif Ishak; Budi Setiadi Daryono (BIOEDUSCIENCE, 2020)
Background: A powdery mildew-resistant cultivar of melon is needed to increase melon yield crops. Meloni is a superior melon cultivar bred through a crossing between â™€ SL-3 and â™‚ PI 371795, resulted by the Laboratory of Genetics and Breeding, Faculty of Biology, UGM. This study aimed to determine the level resistance of Meloni to powdery mildew infection and to identify the powdery mildew species that infected Meloni based on morphological characters. Methods: Meloni seeds were germinated and planted in the greenhouse of PIAT UGM. Powdery mildew spores were inoculated into the leaves after ±2 weeks of age. Leaf infected were scored using the gridline every 3 days for 6 weeks. Scoring results were converted to the diseases index score. Furthermore, powdery mildew species was identified using morphological characters. Results: Meloni had a tolerance level of resistance to the powdery mildew infection. Based on the morphological characters with fibrosin bodies, conidia ovoid-shape and the position of the germ tube in the lateral part of the conidia, powdery mildew that infected Meloni was expected as P. xanthii. Conclusions: Meloni can be expected as an alternative to superior melon seeds resistant to pest and disease infections especially powdery mildew.